PI3K/mTOR-dependent signaling pathway as a possible regulator of processing body assembly - Gudkova, D.O.; Panasyuk, G.G.; Nemazanyy, I.O.; Filonenko, V.V. (Вiopolymers and Cell, 2011)
Aim. To study the role of PI3K/mTOR signaling pathway in regulation of processing body (PB) assembly. Methods. During this study we employed cell imaging technique and Western blot analysis. Results. It was shown that treatment of cells with the specific inhibitors of PI3K/mTOR pathway leads to changes of PBs’ number and size within cells as well as proteasomal degradation of their scaffold protein RCD-8. Conclusions. We speculate that mTOR/PI3K pathway may regulate in part the dynamic of PB formation in the cell by affecting the stability of RCD-8 protein and therefore controle mRNA metabolism. Keywords: processing bodies, immunocytochemistry, mRNA degradation, mTOR, signaling pathway.